Membrane stress equations for a catenary dome with a variation in wall thickness. (15th February 2022) - Gohnert, Mitchell; Bradley, Ryan
Highlights: Membrane theory of a catenary dome. Catenary dome with an oculus, or skylight. Linear variation in thickness of a catenary dome. Abstract: Catenary domes have increased in importance over the last few decades, due to its efficiency in carrying loads. Catenary domes are pure compression structures, which is a favorable characteristic, especially if the building materials are masonry or concrete. The membrane theory for catenaries was previously developed for domes with a constant wall thickness. This paper, however, develops the membrane theory for a catenary dome with a linear variation in wall thickness. Furthermore, the theory is extended to catenary domes with an oculus, or a dome with a concentric hole at the apex. A finite element analysis (FEA) was also performed to determine the accuracy of the proposed theory, which indicates an almost perfect match. The only deviation is at the boundaries, but the difference is not significant.